Parenting for Children’s Character in Multicultural Context: Insights on Trust, Caring, Tolerance, and Forgiveness - Aisyah, Siti; Novita, Dian; Noor, Nina Mariani; Syarah, Erie Siti; Mustapa, Noviana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Parenting is a central site of children’s character formation, especially in culturally diverse societies where values are learned, negotiated, and reinforced through everyday relationships. Drawing on character education and informed by broader discussions in social and emotional learning (SEL) and SDG 4.7, this study examined how value-based parenting dimensions, namely trust, caring, tolerance, helpfulness, and forgiveness, are associated with children’s character development in Indonesia’s multicultural context. A cross-sectional survey was conducted with 112 female primary caregivers from five regions of Indonesia, Kuningan, Bogor, Tasikmalaya, Manado, and Jayapura, and the proposed model was analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that trust, caring, tolerance, and forgiveness are significant positive predictors of children’s character development, reflected in honesty and integrity, empathy and care, respect for difference, and constructive conflict resolution. Helpfulness, however, did not show a statistically significant direct effect once the other parenting dimensions were examined simultaneously. These findings suggest that children’s character development is better understood through an integrated moral-relational configuration of parenting values than through any single value considered in isolation. The study contributes to scholarship by clarifying which parenting values retain distinct explanatory relevance within a combined model and by showing that helpfulness may operate in a more indirect or context-dependent way. It also offers a modest global contribution by bringing evidence from a multicultural Indonesian setting into wider debates on family-based character development in diverse societies. The findings have practical implications for parenting education, early childhood programmes, and family-school partnerships that seek to strengthen value-based character formation.